Kajian Literatur Kualitas Air Limbah: Perbandingan Parameter Uji dan Standar Baku Mutu - Maisarah, Sri; Kamiana, I Made; Jaya, Allan Restu (Jurnal Basement : Jurnal Teknik Sipil, 2025)
This study aims to analyze the quality of domestic and industrial wastewater based on the compliance of physical, chemical, and biological parameters with established quality standards. The method employed is a literature review of seven scientific articles discussing parameters such as temperature, pH, COD, BOD, TSS, ammonia, and total coliform. The analysis results indicate that compliance levels vary across locations and wastewater types. In domestic wastewater, 33.33% to 100% of the parameters meet the standards, while in industrial wastewater, 25% to 100% of the parameters exceed the permissible limits. BOD is the most frequently non-compliant parameter compared to COD. Tofu industry wastewater shows the highest pollution level, whereas dairy industry wastewater demonstrates higher compliance with quality standards. The effectiveness of wastewater treatment methods also varies, with several studies recommending the optimization of biological and chemical processes, such as the use of biofilters and coagulants, to enhance treatment efficiency. This study concludes that most wastewater parameters do not meet quality standards, indicating the need for improved treatment technologies to prevent environmental contamination